Effects of temperature and deposition time on the RF- sputtered CdTe films preparation (Superficies y Vacío, 2014)
In this work, CdTe thin films were deposited by rf-sputtering at different substrate temperatures (room temperature (RT), 100, 150, 200, and 250 °C) and deposition times (30, 60, and 90 min). The applied power and vacuum pressure were maintained fixed for all depositions. A mean value of 18.5 nm/s on the deposition rate was maintained for films deposition. The surface morphology, rms-roughness, and grain size of the sputtered-films were obtained from atomic force microscopy and scanning electron microscopy images for comparison. CdTe films deposited during 60 min presented high reproducibility, because their consistent thickness value (1.2 ?m) at different substrate temperatures. Higher thickness than 1.81 ?m was obtained for films deposited at 250 °C and 90 min. CdTe films deposited at 150 °C present minor dispersion on thickness, while rms-roughness increased with the increase of substrate temperature but only for films deposited at 60 and 90 min. CdTe film deposited at 250 °C during 90 min was selected as appropriate for CdS/CdTe solar cells preparation.